Moisture movement in concrete during drying - Holmes, Niall (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2009)
The prediction of moisture distribution within concrete slabs has considerable practical importance as it affects the time at which coverings can be safely applied. Moisture in concrete affects creep, shrinkage, strength development, durability and must be present in sufficient quantities for full hydration to occur and for workability on site. However, an excess of moisture in concrete at the point of covering particularly can lead to a number of problems such as delamination and blistering of vinyl, buckling of timber floors and rising of tiles. Moisture migrates in concrete slabs as a diffiision-type process during drying and is lost to the ambient air via evaporation from exposed surfaces. Drying will continue until equilibrium is reached between the humidity in the concrete and in the ambient air. The measured relative humidity (rh) profiles indicate that non-linear profiles exist early on as drying was more rapid near the surface, particularly during accelerated drying. Over time, however, the moisture movement became more uniform through the slab.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin